Uji Fisik Sediaan Gel Ekstrak Tongkol Jagung (Zay Mays L) - Indri Kusuma Dewi; Mey Rachmawati; Fathiya Abdinnisa' Ma'rifah; Puspita Susilowati (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstract Background : Corn cobs have the potential to protect the skin, so far the research has only been limited to testing the extracts and has not been formed in a cosmetic preparation. Gel is a cosmetic preparation that is ideal for sunscreens because it is less oily, not sticky, soft, elegant, can form a layer of film that adheres well and protects the skin, and evaporation of water content creates a soothing and pleasant effect. Method: The method is used to determine the physical appearance of the gel with organoleptic parameters, homogeneity, dispersion and absorbency. Result: The purpose of this study was to determine the results of the physical test of sunscreen gel preparations from corn cobs extract (Zea mays L). Conclusion: The physical test results from the sunscreen gel extract of corn cobs extract (Zay Mays L.) had the results of organoleptic test, homogeneity test, spreadability test and adherence to the standard.